Where Caciques and mapmakers met : border making in eighteenth-century South America - Erbig, Jeffrey Alan, Jr (David J. Weber series in the new borderlands history., 2020)
"During the late eighteenth century, Portugal and Spain sent joint mapping expeditions to draw a nearly 10,000-mile border between Brazil and Spanish South America. These boundary commissions were the largest ever sent to the Americas and coincided with broader imperial reforms enacted throughout the hemisphere. Where Caciques and mapmakers met considers what these efforts meant to Indigenous peoples whose lands the border crossed. Moving beyond common frameworks that assess mapped borders strictly via colonial law or Native sovereignty, it examines the interplay between imperial and Indigenous spatial imaginaries. What results is an intricate spatial history of border making in southeastern South America (present-day Argentina, Brazil, and Uruguay) with global implications"--